The Instruments of Transport Policy - Štefančić, Gordana; Krobot, Ivana; Hrženjak, Zlatko (Promet - Traffic&Transportation, 2006)
The work proposes the transport policy instruments, suchas the infrastructure measures, management measures and informationprovision measures as the means that could reduceor eliminate transport problems. All these measures have beenfollowed through the provisions for passenger cars, provisionsfor public transport, provisions for cyclists and pedestrians andprovisions regarding transport. A range of solutions is given toreduce congestion, improve accessibility and improve the trafficconditions for those who depend on public transport along withthe improvement of environmental conditions.